The interference of violence in the nursing work routine (Research, Society and Development, 2020)
Violence affects the dignity of professionals in the world, as a source of inequality, discrimination, stigmatization and conflict at work. Violence, whether physical or psychological, is a problem that crosses borders, work contexts and groups of professionals. The objective was to identify the most frequent types of occupational violence suffered by nursing workers and how the risks can affect the work process. This is an exploratory type research with a qualitative approach, with the emergency sector of a University Hospital located in the interior of Rio de Janeiro as its scenario. Eighteen nursing professionals participated, of both sexes. Using a questionnaire to obtain the data. The ethical aspects of the research were respected, approved with opinion number 3,295,302. With data treatment through analytical reading of data based on the Bardin Content Analysis framework and the current guidelines of the Ministry of Health on Violence at Work in the Health Sector. The results demonstrate how much exposure of the professional to numerous types of violence, verbal, physical, rudeness, name calling, psychological, tooth others. Finally, violence in the work environment makes nursing professionals vulnerable to developing health problems, involving physical and / or psychological problems, which can influence the performance of the chores and routines of their work and also in their care.